2021
DOI: 10.1128/jvi.01651-20
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Receptor-Binding Preference and Zoonotic Potential of H9N2 Avian Influenza Viruses

Abstract: Receptor recognition and binding is the first step of viral infection and a key determinant of host specificity. The inability of avian influenza viruses to effectively bind human-like sialylated receptors is a major impediment to their efficient transmission in humans and pandemic capacity. Influenza H9N2 viruses are endemic in poultry across Asia and parts of Africa where they occasionally infect humans and are therefore considered viruses with zoonotic potential. We previously described H9N2 viruses, includ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
(106 reference statements)
0
21
0
Order By: Relevance
“…Compared to the H7N9 parental virus, the binding preference of the genotype 122 H9N9 virus was comparable for the 6SLN but weaker for 3SLN sialoglycans, but the reassortant H9N9 again showed its increased binding toward the 3SLN(6-su) receptor analogue. Viruses with preferable binding toward 3SLN(6-su) may have an increased propensity for circulation in terrestrial poultry ( 77 , 78 ), and this observation was reflected in the successful generation and transmission of these H9N9 genotypes in chickens in our in vivo experiment. Previous analysis of N9 NA showed that hemadsorption sites could be responsible for increasing the overall avidity of the virus toward the sialoglycans ( 79 , 80 ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Compared to the H7N9 parental virus, the binding preference of the genotype 122 H9N9 virus was comparable for the 6SLN but weaker for 3SLN sialoglycans, but the reassortant H9N9 again showed its increased binding toward the 3SLN(6-su) receptor analogue. Viruses with preferable binding toward 3SLN(6-su) may have an increased propensity for circulation in terrestrial poultry ( 77 , 78 ), and this observation was reflected in the successful generation and transmission of these H9N9 genotypes in chickens in our in vivo experiment. Previous analysis of N9 NA showed that hemadsorption sites could be responsible for increasing the overall avidity of the virus toward the sialoglycans ( 79 , 80 ).…”
Section: Discussionmentioning
confidence: 90%
“…The results suggested that the reassortant H9N9 virus has a relatively more acid stable HA, similar avidity for human-like (6SLN) and less avidity for avian-like (3SLN) compared to Anhui/13 H7N9 virus. Further, the H9N9 virus has strongest binding toward 3SLN(6-su) receptors, thereby maintaining adaptation of such viruses for poultry ( 78 ) while also enabling additional zoonotic potential ( 83 , 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, mutations in the HA head and RBS variations would help virus evade these antibodies ( 21 ). Single or combined mutations at positions 166, 168, 198, 201, and 234 were involved in switching the antigenic phenotype and receptor specificity of seasonal H3N2 virus and H9N2 IAV ( 34 36 ). The HA mutations identified in this study also decreased the HI titers of serum samples from challenged mice, H9-specific MAbs, and chicken serum, which indicated that HA mutations caused by NA antibody pressure can also help virus evade neutralizing antibodies against HA.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Q227 in combination with either aspartic acid (D) or glutamic acid (E) at position 190 favors binding α2,6SAs receptors. Other changes such as A160D/N, Q156R, T205A, V245I, V216L, D208E, T212I, R1721 and S175N also enhance the human-like receptor binding in vitro [76,77]. The terminal sialic acid linkage is not the only factor that affects the binding of IAV HA to the host cell; other features such as the sialic acid structure (e.g., N-acetylneuraminic acid versus N-glycolylneuraminic acid) or length may also play a role (reviewed in [55]).…”
Section: Molecular Mechanisms Associated With Interspecies Transmission Of Iavsmentioning
confidence: 99%